Women’s empowerment in agriculture and child nutritional status in rural Nepal - Cunningham, Kenda; Ploubidis, George B.; Menon, Purnima; Ruel, Marie T.; Kadiyala, Suneetha; Uauy, Ricardo; Ferguson, Elaine (Cambridge University Press, 2015)
To examine the association between women’s empowerment in agriculture and nutritional status among children under 2 years of age in rural Nepal.Cross-sectional survey of 4080 households conducted in 2012. Data collected included: child and maternal anthropometric measurements; child age and sex; maternal age, education, occupation and empowerment in agriculture; and household size, number of children, religion, caste and agro-ecological zone. Associations between the Women’s Empowerment in Agriculture Index (WEAI)’s Five Domains of Empowerment (5DE) sub-index and its ten component indicators and child length-for-ageZ-scores (LAZ) and weight-for-lengthZ-scores (WLZ) were estimated, using ordinary least-squares regression models, with and without adjustments for key child, maternal and household level covariates.Two hundred and forty rural communities across sixteen districts of Nepal.Children under 24 months of age and their mothers (n1787).The overall WEAI 5DE was positively associated with LAZ (β=0·20,P=0·04). Three component indicators were also positively associated with LAZ: satisfaction with leisure time (β=0·27,P<0·01), access to and decisions regarding credit (β=0·20,P=0·02) and autonomy in production (β=0·10,P=0·04). No indicator of women’s empowerment in agriculture was associated with WLZ.Women’s empowerment in agriculture, as measured by the WEAI 5DE and three of its ten component indicators, was significantly associated with LAZ, highlighting the potential role of women’s empowerment in improving child nutrition in Nepal. Additional studies are needed to determine whether interventions to improve women’s empowerment will improve child nutrition.